Synthesis and Bioinformatics Study of 2-Nitrocinnamaldehyde Derivatives as an Anti MCF-7 Breast Cancer Cells - Wardani, Alidya Fitri Kusuma; Naufal, Muhammad; Latief, Madyawati; Tarigan, Indra Lasmana; Juliandri, Juliandri; Al-Anshori, Jamaludin (Trends in Sciences, 2025)
Conventional and systemic treatments of breast cancer are commonly found to expose unexpected side effects. Thus, a new drug design is intensively explored to anticipate the related risks. This work aimed to synthesize and characterize the chalcone derivatives based on a cinnamaldehyde skeleton (9 - 12). Further biological assay of the derivatives against MCF-7 breast cancer cell lines and their molecular docking analysis was also performed to obtain a more potential chemical structure for the active compounds. Four compounds of a 2-Nitrocinnamaldehyde-based scaffold, 1-(4-aminophenyl)-5-(2-nitrophenyl)-penta-2,4-dien-1-one (9), 1-(4-bromophenyl)-5-(2-nitrophenyl)-penta-2,4-dien-1-one (10), 5-(2-nitrophenyl)-1-(p-tolyl)-penta-2,4-dien-1-one (11), and 5-(2-nitrophenyl)-1-(pyridine-3-yl)-penta-2,4-dien-1-one (12) were successfully synthesized with a chemical yield of 29 - 99 %. The synthetic method employed a one-pot Claisen-Schmidt coupling reaction using a NaOH/KOH base catalyst, while their characterization was based on spectroscopic data and literature comparison. An in-vitro MTT bioassay against MCF-7 cancer cells revealed the IC50 values of the derivatives of 9, 10, 11, and 12 were 178, 376, >500, and 118.20 μg/mL, respectively. Molecular docking showed that the most potent compound in this series (12) had the lowest binding energy (–8.56 kcal/mol) and created an essential H-bond with hinge region residue, Met793. Docking-based structural optimization of 12 showed that incorporating 3 important pharmacophores commonly found in EGFR kinase inhibitors, fused heterocyclic, hydrophobic group, and propylmorpholine moiety, resulted in lower binding energy (–9.41 kcal/mol). Perhaps the modified 12 could exhibit a more potent toxicity against MCF-7. HIGHLIGHTS Anti-MCF-7 breast cancer potential of new cinnamaldehyde derivatives. A one-pot Claisen-Schmidt coupling reaction of new chalcone derivatives. A bioinformatics study of a more potent structure modification. GRAPHICAL ABSTRACT